Dampak Teknologi Informasi Berbasis Artificial Intelligence terhadap Kepuasan dan Loyalitas Wisatawan: Tinjauan Systematic Literature Review - Fahrurozi, Slamet Kurniawan; Epin Andrian, Dimas Pamilih (MASALIQ, 2025)
This study aims to analyze the impact of Artificial Intelligence (AI)-based information technology on tourist satisfaction and loyalty through a systematic literature review method. Following the PRISMA guidelines, researchers conducted a literature search in the ScienceDirect and SpringerLink databases using keywords such as "artificial intelligence," "tourist satisfaction," and "tourist loyalty." Of the 40 articles identified, 12 articles met the inclusion criteria and were analyzed thematically. The results showed that AI significantly improves tourist satisfaction through service personalization, operational efficiency, and better interactions. Applications such as recommendation systems, chatbots, and predictive analytics have proven effective in improving the tourist experience. However, the implementation of AI also faces challenges such as data privacy, algorithmic bias, and low technology adoption. The implications of this study are the importance of optimizing the use of AI by ensuring data security, reducing bias, and improving education for service providers and tourists. This study provides recommendations for further research, including exploring the impact of AI on specific tourist segments and investigating the long-term impact on loyalty.